Immunohistochemical evaluation of colorectal carcinoma: experience of a four-year study - Sravani, Muchalapuri; Fatima, Fatima; Fatima, Rasheed; Deepthi, K. N.; Karamchedu, Shilpa; Nishadbanu, Shaikh; Swetha, Allam (Pathologia, 2024)
Colorectal carcinomas (CRC) is the third most common cause of death in developed countries. Invoking of primary site of carcinoma of unknown origin using immunohistochemistry is essential for accurate diagnosis, and also for targeted therapies. Aim. This study aimed to assess immunohistochemical expression of CK7, CK20, and CDX2 in colorectal carcinomas, and to evaluate their diagnostic role. Materials and methods. A retrospective study was performed on 36 paraffin blocks of documented colorectal carcinomas were stained by immunohistochemical technique using a tissue microarray with CK7, CK20 and CDX2 markers. The resulted data were statistically analyzed. Results. There was a negative association between CDX2 expression and histologic grade (p = 0.03), as well as T-pathologic stage (p = 0.01). CK7-ve / CK20+ve immune profile showed a specificity of 95 % in predicting the colorectal adenocarcinomas, which was superior to that of CDX2. CDX2 loss is related to tumour grade and depth (T-stage). Conclusions. Both CDX2 expression, and CK7-ve / CK20+ve are the most sensitive, and specific markers to diagnose the colorectal carcinoma. CK7-ve / CK20+ve expression is used as specific marker for colorectal carcinoma for targeted therapy.